Korelasi Antara Asupan Zat Gizi Makro dengan Jumlah Bakteri Komensal (Lactobacillus Spp. dan E. Coli) pada Feses Ibu Hamil - Ayu Delima, Andi Alifia; Dachlia Sri Sakti; Evita Sarah Nasution (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Nutritional intake during pregnancy is important for maternal and fetal health, which is influenced by the digestive system and commensal bacteria. Lack of nutritional fulfillment can cause serious complications, such as low birth weight, stunting, and maternal death. Based on Riskesdas 2018, the prevalence of chronic energy deficiency in pregnant women in Indonesia reached 24.4%. This study looked at the correlation between macronutrient intake and the presence of commensal bacteria in the feces of pregnant women. A descriptive observational study with a cross-sectional design was conducted on 22 respondents selected through purposive sampling. Macronutrient intake data were collected using 24-hour recall and Food Frequency Questionnaire (FFQ). Fecal samples were collected independently in sterile containers, stored at 2-8°C, and analyzed in the HUMRC laboratory of Hasanuddin University Hospital using the PCR method, and Kendall's tau correlation test analysis was carried out with SPSS version 25. The results showed that 90.9% of respondents had inadequate carbohydrate intake, 86.3% had insufficient protein intake, and 68.2% had adequate fat intake. A total of 95.4% had energy intake below the recommendation. E. coli was more dominant than Lactobacillus spp. Statistical analysis didn't find a significant correlation between macronutrient intake and the number of commensal bacteria. This study shows the need to improve the nutritional quality of pregnant women and further research to understand the impact of gut microbiota on maternal and fetal health.